The Relationship among Learning Styles, Classroom Environment, and Academic Achievement of English Education Study Program Students in State Islamic University of Raden Fatah Palembang - HERIZAL HERIZAL (Ta'dib: Jurnal Pendidikan Islam, 2018)
This research is a correlational study with 441 students used as the population of the study. 366 students were selected as sample by using purposive sampling technique. In collecting the data, questionnaires (the learning styles and the classroom environment questionnaire) and documentation (student's GPA) were used to find the correlation and the influence among learning styles, classroom environment, and students’ academic achievement. From the results of correlational analysis between learning styles and students' academic achievement using Pearson Product Moment Correlation, it was found that the significant correlation between the two variables was not found. Then, the second correlational analysis between classroom environment and students’academic achievement showed that there was a significant correlation between the two variables with p-output = .313 which was significant at .01 level. Since the significant correlation between learning styles and students’ academic achievement were not found, the regression analysis to find the influence was not further conducted. Meanwhile, since classroom environment and students’ academic achievement were significantly correlated, the regression analysis was then conducted. Based on the regression analysis, it was found that R square was .098, which means that classroom environment influenced the students’ academic achievement with 9.8% contribution.